Tipologi Arsitektur Vernakular Melayu Uma Kabuong Limo di Kampung Pulau Belimbing, Kabupaten Kampar - Wahyu Hidayat; Mashuri Mashuri; Indra Kuswoyo; Muhd. Arief Al Husaini (ATRIUM: Jurnal Arsitektur, 2022)
Title: Typology of Malay Vernacular Architecture Uma Kabuong Limo in Pulau Belimbing Village, Kampar District   One form of residential culture can be seen in the architecture as a residence for the people of Belimbing Island Village, Kampar regency. The house as a residential function always develops according to the needs and image of the owner, so changes in the Uma Kabuong Limo building are found. Uma Kabuong Limo can be categorized as vernacular architecture because Uma Kabuong Limo is a product and name that has existed for several generations with a development process that adapts the socio-cultural and cultural of the Malay community. The nature of this simplicity is not only a residential building but also becomes the identity of the community. Through the study of the architectural typology of Uma Kabuong Limo was studied through the approach of the computational model of heritage building information modeling (HBIM). This modeling is expected to get an in-depth and precise analysis to describe the typology process more accurately. This assessment process begins with field data observation, modeling, and discussion of building typologies. The Uma Kabuong Limo buildings observed are six buildings representing the distribution of facilities in The Belimbing Island Village. The findings were the existence of a slightly different basic shape equation in the kitchen. One of the buildings changed the shape of the roof, called the paranginan roof, a multi-storey roof. The more engravings and tidiness of home making depict, the higher the level of the social status of the building owner.